Hubungan Antara Kapasitas Vital Paksa dengan Kualitas Hidup Penderita Penyakit Paru Obstruksi Kronis - Hasmana, Saputra Aji; , Isnaini Herawati, S.Fis., M.Sc; , Wahyuni, S.Fis., M.Kes (2015)
Background: chronic obstruction lung disease (PPOK) one of disease is not contamination to be one health problem in Indonesia. Patient's chronic obstruction lung have disruption or obstruction sniff of air. Limitation air flow will be reducing lung function so it causes reduction value KVP. Lung function reduces of lung function to be a problem from symptoms, impact to patient's activities. Research purpose: To know correlation KVP with live quality of PPOK patients. Research Method: This research uses cross sectional approach and collecting data analysis with product moment. Result Research: Base on analysis data test uses product moment, result is p value of KVP to live quality is 0.881 so p value < 0.05 means correlation between KVP to live quality. Conclusion: It is correlation between KVP to live quality to patient's PPOK.